2016
DOI: 10.1177/1756287216652030
|View full text |Cite
|
Sign up to set email alerts
|

Treatment compliance of working persons to high-dose antimuscarinic therapies: a randomized trial

Abstract: As a result of this study, under the control of the objective functional state of LUT, the influence of various factors on the patients' stability in the treatment with AM drugs was revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, a decrease in the sexual life quality and libido (against the background of dutasteride administration), as well as the maintenance of hyperactivity symptoms can lead to psycho-emotional lability of patients, reactive depression, and refusal of further treatment. There are numerous studies, including our own, which indicated a significant decrease in medication adherence, and even a rejection of it in case of the absence of a relatively rapid positive effect [ [25] , [26] , [27] ]. Nevertheless, methods for rapid and safe correction symptoms of obstruction and hyperactivity and sexual dysfunction in the dutasteride treatment of BPH are not currently fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, a decrease in the sexual life quality and libido (against the background of dutasteride administration), as well as the maintenance of hyperactivity symptoms can lead to psycho-emotional lability of patients, reactive depression, and refusal of further treatment. There are numerous studies, including our own, which indicated a significant decrease in medication adherence, and even a rejection of it in case of the absence of a relatively rapid positive effect [ [25] , [26] , [27] ]. Nevertheless, methods for rapid and safe correction symptoms of obstruction and hyperactivity and sexual dysfunction in the dutasteride treatment of BPH are not currently fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…Higher education level is a well-known factor associated with adherence to MRA and other drugs. Previous studies have reported better compliance to antimuscarinic therapy among individuals with higher incomes [ 28 ], which is highly related to educational level. Better adherence among patients with a short duration of OAB symptoms may be explained by a shorter period of therapy duration.…”
Section: Discussionmentioning
confidence: 99%
“…After consultation with an expert panel of urologists and observation of clinical practice in Iran, solifenacin 5 and/or 10 mg was selected as the comparison arm in the first-line of treatment and tolterodine 2 and/or 4 mg as the second-line. The data from randomized controlled trials (SYNERGY II) and meta-analysis of international studies were used to obtain efficacy and clinical safety parameters (16)(17)(18)(19).…”
Section: Model Overview and Outcomesmentioning
confidence: 99%